Analisis Dividend Payout Ratio (DPR), Gross Profit Margin (GPM), dan Net Profit Margin (NPM) Terhadap Harga Saham Indeks PEFINDO-25 - Romi Ferdian; Edy Suryadi; Heni Safitri (Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study was to determine the effect of Financial Ratios using the ratio of Dividend Payout Ratio (DPR), Gross Profit Margin (GPM), and Net Profit Margin (NPM) to Share Prices on the PEFINDO-25 Index. The sampling technique used in this study is the Saturated Sample Method. For simultaneous test results using the F test shows that the three independent variables, namely the DPR, GPM, and NPM together do not significantly influence the dependent variable (Share Price) as evidenced by the calculated F value of 4.881 and having a sig. amounting to 0.010 which is greater than 0.05, while for partial testing using the t test shows that the independent variables, namely the DPR and NPM, have no significant effect while GPM has a significant influence on stock prices. For the R test (correlation), the results of the three variables obtained were 0.713. This means that the relationship between Dividend Payout Ratio, Gross Profit Margin and Net Profit Margin to Share Prices has a strong relationship with a value of 0.713. For the determination coefficient determination (R2) results, the results obtained from the three independent variables are DPR, GPM, and NPM of 0.508. This means that the influence of Dividend Payout Ratio (DPR), Gross Profit Margin (GPM), and Net Profit Margin (NPM) is only 50.8% of the Share Price, the remaining 49.2% Share Price can be influenced by variables others that were not examined in this study.